Hands-On Training Courses for Cervical Cancer Screening, Diagnosis, and Treatment Procedures in Low- and Middle-Income Countries. (5th January 2022) - Phoolcharoen, Natacha; Varon, Melissa Lopez; Baker, Ellen; Parra, Sonia; Carns, Jennifer; Cherry, Katelin; Smith, Chelsey; Sonka, Theresa; Doughtie, Kathleen; Lorenzoni, Cesaltina; Richards-Kortum, Rebecca; Schmeler, Kathleen; et al.
Abstract : In 2018, there were approximately 570, 000 new cases of cervical cancer worldwide. More than 85% of cases occurred in low- and middle-income countries (LMICs), primarily because of poor access to screening and a limited number of medical providers trained to diagnose and treat cervical precancerous lesions. Our objective was to provide locally arranged, hands-on training courses for medical providers in LMICs to learn to perform cervical cancer screening, diagnosis, and treatment procedures. The courses included didactic lectures and hands-on training stations using low-cost simulation models developed by bioengineers and students at Rice University in Houston, TX, United States, and the Malawi Polytechnic in Blantyre, Malawi. The hands-on training stations included visual inspection with acetic acid (VIA), colposcopy, cervical biopsy, endocervical curettage, loop electrosurgical excision procedure (LEEP), and thermal ablation. Provider pre- and postcourse confidence levels in performing the procedures were evaluated. From February 2017 to January 2020, we arranged 15 hands-on training courses in seven cities across six countries (El Salvador, Mozambique, Trinidad and Tobago, Lesotho, Malawi, and Nepal). Overall, there were 506 participants. The average number of participants per course was 38 (range 19-92). The participants included doctors, nurses, and midwives. The course duration varied from 1 to 3 days. Increased confidence in performing VIA, colposcopy and cervical biopsy, ablation, and LEEP was reported by 69%, 71%, 61%, and 76% of participants, respectively. Our findings suggest that locally arranged, hands-on cervical cancer prevention training courses in LMICs can improve provider confidence in performing cervical cancer screening, diagnosis, and treatment procedures. These courses are part of a larger strategy to build local capacity for delivering and improving cervical cancer prevention services in LMICs. Abstract :